A COMPARISON OF HOW DETERMINANTS OF CAPITAL STRUCTURE AFFECT LEVERAGE AND SHARE PRICE: EVIDENCE ON UK FIRMS. - Mbatia, Joy (2014)
This study seeks to determine how various capital structure determinants affect leverage and share price from 2009-2013. I will use FTSE 350 companies and will focus on sectors such as Aerospace & Defence, Beverages, Construction & Materials, Food & Drugs retailers, Household Goods, Mobile telecommunications, Support services, Technology & Hardware Equipment and Travel & Insurance. I will test various determinants such as liquidity, profitability, size, tangibility, growth, age, non-debt tax shields and business risk. Using correlation analysis and fixed effect regression estimation model, I established a relationship between determinants and leverage then a relationship between the determinants and share price. The relationships are then analysed and compared to each other. While Liquidity, non-debt tax shields and growth are significant on leverage under both models, Profitability and size are significant on share price. From my findings, I would recommend a firm that wants to use equity financing to make sure it has a high profitability in order to attract shareholders. This way they will be able to sell shares at higher prices and get more capital.